Ketamine Induced Bladder Fibrosis Through MTDH/P38 MAPK/EMT Pathway - Zhu, Quan; Li, Kaixuan; Li, Haozhen; Han, Feng; Tang, Zhengyan; Wang, Zhao (Frontiers in Pharmacology, 2022)
Purpose: Ketamine is an anesthetic in clinical, but it has also been used as an abusing drug due to its low price and hallucinogenic effects. It is proved that ketamine abusing would cause multiple system damage including the urinary system, which is called ketamine-induced cystitis (KIC). Bladder fibrosis is late stage in KIC and threaten abusers’ life. This study aimed to investigate the molecular mechanism of ketamine-induced bladder fibrosis. Methods: Female Sprague Dawley (SD) rats were randomly divided into 3 groups. 2 groups were treated with tail vein injection of ketamine (25 mg/kg/day, 50 mg/kg/day ketamine hydrochloride solution, respectively) for 12 weeks, whereas the control group was treated with normal saline solution. In each group, rat bladders were extracted and samples were examined for pathological and morphological alterations via hematoxylin and eosin (HE) staining, Masson's trichrome staining and immunohistochemistry (IHC). SV-HUC-1 cells were treated with different concentrations of ketamine solution (0, 0.1, 0.5, 1 mmol/L). Rat bladder and SV-HUC-1 cells were extracted protein and RNA for Western blot and RT-PCR detection. Metadherin (MTDH) siRNAs and overexpression plasmids were used to knock down and overexpress the relative genes. P38 mitogen-activated protein kinase (MAPK) inhibitor was utilized to inhibit the MAPK pathway. Results: Rats in the ketamine group exhibited fibrosis compared to rats of the control group and fibrosis were also markedly upregulated in SV-HUC-1 cells after treated with ketamine, which were ketamine concentration-dependent. After treating with ketamine in SV-HUC-1 cells, there was an increase expression of MTDH, epithelial-mesenchymal transition (EMT) markers, P38 MAPK. MTDH knockdown would suppresses P38 MAPK/EMT pathway to inhibit fibrosis, however, MTDH overexpression could promote the pathway in SV-HUC-1 cells. Conclusion: In rats and SV-HUC-1 cells ketamine-treated models, MTDH can regulate EMT through the P38 MAPK pathway to regulate the process of bladder fibrosis.